Estimation of the influence of hypoglycemia and body mass index on health-related quality of life, in patients with type 2 diabetes mellitus - Cvetanović, Goran Z; Stojiljković, Marija; Miljković, Mirjana (Vojnosanitetski pregled, 2017)
Background/Aim. Recent data have shown that obese patients with type 2 diabetes mellitus (T2DM) have more commonly impaired glycemic control and complication such as neuropathy as well as a higher mortality rate than normal body weight patients with diabetes. The aim of this study was to quantify patient-reported rates of hypoglycemia, determine body mass index (BMI) and evaluate their association with health-related quality of life (HRQL) estimated by EuroQoL-EQ 5-dimensional (EQ-5D) questionnaire in individuals with T2DM after adjusting for age, duration of diabetes mellitus and presence of late diabetes complications. Methods. This clinical-epidemiological cross sectional study involved 269 consecutively selected adult patients of both sexes with T2DM duration longer than one year. The standardized Serbian version of the EQ-5D 3 level version – EQ-5D-3L questionnaire with a visual analogue scale-VAS (EQ-VAS), was used to assess respondents’ HRQL and utility values. Results. The average age of participants was 65.1 ± 9.3 years; hypoglycemia was registered in 71.0%, obesity in 43.9% and chronic complications in 88.8% of the patients. Half of the patients did not reach the target value of glycated hemoglobin (HbA1c) < 7.0%. Patients that experienced episodes of hypoglycemia years compared to those with good glycemic control were significantly younger at diagnosis (54.19 vs 57.59 years, respectively) and less likely to be graduated at tertiary school (7.3% vs 35.1%, respectively). They had higher mean EQ-5D subscale score (pain/discomfort: 1.86 vs 1.68, respectively), lower VAS (55.99 vs 62.44) and EQ-5D index (0.85 vs 0.87, respectively). Obese patients were more likely to be female with higher systolic and diastolic pressure, triglycerides, waist circumference, subscale score (anxiety/depression 2.01 vs 1.80) and rates of hypoglycemia per year. After adjusting for confounders, the presence of hypoglycemia had 2,035 greater odds for experienced problems related to pain/discomfort. The unit increase of BMI had 1.05 greater odds for experienced problems related to mobility and anxiety/depression. Hypoglycemia was associated with significantly lower levels of the VAS score (b = -0.13). Increasing of BMI was associated with significantly lower EQ-5D index value (b = -1.78). The rates of hypoglycemia were not associated with VAS score and EQ-5D index values. Conclusion. Results demonstrated a significant association of hypoglycemia and obesity with impaired HRQL determined by the EQ-5D questionnaire. Lifestyle measures aimed to reduce obesity and hypoglycemia together with optimal diabetic therapy regiment can markedly improve patients’ HRQL.